γA/γ’ fibrinogen inhibits thrombin-induced platelet aggregation - Lovely, Rehana S.; Rein, Chantelle M.; White, Tara C.; Jouihan, Sari A.; Boshkov, Lynn K.; Bakke, Antony C.; McCarty, Owen J.; Farrell, David H. (Thrombosis and Haemostasis, 2008)
The minor γA/γ’ fibrinogen isoform contains a high affinity binding site for thrombin exosite II that is lacking in the major γA/γA fibrinogen isoform. We therefore investigated the biological consequences of the γ’ chain binding to thrombin. Thrombin-induced platelet aggregation was inhibited by γA/γ’ fibrinogen.Carboxyl terminal peptide fragment γ’410–427 from the γ’ chain was also inhibitory, with an IC50 of ∼200 µM in whole plasma. Deletion of the peptide from either the amino or carboxyl end significantly decreased inhibition. In contrast to thrombin-induced platelet aggregation, aggregation induced by epinephrine, ADP, arachidonic acid, or SFLLRN peptide showed little inhibition by the γ’ peptide. The inhibition of thrombin-induced platelet aggregation was not due to direct inhibition of the thrombin active site, since cleavage of a small peptidyl substrate was 91% of normal even in the presence of 1 mM γ’410–427.The γ’410–427 peptide blocked platelet adhesion to immobilized thrombin under both static and flow conditions,blocked soluble thrombin binding to platelet GPIbα, and inhibited PAR1 cleavage by thrombin. These results suggest that the γ’ chain of fibrinogen inhibits thrombin-induced platelet aggregation by binding to thrombin exosite II. Thrombin that is bound to the γ’ chain is thereby prevented from activating platelets, while retaining its amidolytic activity.
Keywords: Antiplatelet agents; antithrombin; fibrinogen/fibrin; protease activated receptors (PAR); thrombin